2003
DOI: 10.1086/378783
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic versus Instantaneous Models of Diet Choice

Abstract: We investigate the dynamics of a series of two-prey-one-predator models in which the predator exhibits adaptive diet choice based on the different energy contents and/or handling times of the two prey species. The predator is efficient at exploiting its prey and has a saturating functional response; these two features combine to produce sustained population cycles over a wide range of parameter values. Two types of models of behavioral change are compared. In one class of models ("instantaneous choice"), the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…Instability due to adaptive behavior by the middle species in a three-species food chain was demonstrated in Abrams (2003); in this case, the instability was due to a trade-off between foraging and defense that involved a fitness-minimizing equilibrium. Abrams (1999) and Ma et al (2003) showed that the lags in food choice could greatly alter the dynamics of a one-predator-two-prey model that cycled even in the absence of behavioral choice. Finally, Abrams (2007) and Abrams et al (2007) provided examples of instability arising from the combination of adaptive movement between patches and interspecific interactions within patches for systems with a three-species food chain (Abrams 2007) and a pair of competing species ).…”
Section: Twelve Questions About Choice Of Resourcementioning
confidence: 99%
“…Instability due to adaptive behavior by the middle species in a three-species food chain was demonstrated in Abrams (2003); in this case, the instability was due to a trade-off between foraging and defense that involved a fitness-minimizing equilibrium. Abrams (1999) and Ma et al (2003) showed that the lags in food choice could greatly alter the dynamics of a one-predator-two-prey model that cycled even in the absence of behavioral choice. Finally, Abrams (2007) and Abrams et al (2007) provided examples of instability arising from the combination of adaptive movement between patches and interspecific interactions within patches for systems with a three-species food chain (Abrams 2007) and a pair of competing species ).…”
Section: Twelve Questions About Choice Of Resourcementioning
confidence: 99%
“…The work presented here highlights the complexity of behavioural (within-generation) dynamics that can be lost in (between-generation) population dynamic models (Mangel and Roitberg 1992;Bolker et al 2003;Ma et al 2003;Persson and De Roos 2003). Adaptive host selection (or in the case of predator-prey interactions, adaptive diet choice) is thought to be a stabilizing process (Comins and Hassell 1979;Fryxell and Lundberg 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of smaller parasitoids may mitigate this effect, as they will generally select smaller hosts. Temporal refuges will create time-lagged responses by parasitoids (or predators), which may destabilize population dynamics (Gurney and Nisbet 1985;Ma et al 2003;Pachepsky et al 2008). The influence of this trait-mediated interaction on between-generation dynamics has yet to be fully explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptive behaviour is considered to be important for shaping local (Abrams and Matsuda, 2004;Abrams, 2000;Ma et al, 2003;Post et al, 2000;Teng and McCann, 2004) and regional Abrams et al, 2012;Amarasekare, 2008Amarasekare, , 2007Ruokolainen et al, 2011) population dynamics, food web structure (e.g., Beckerman et al, 2006;Heckmann et al, 2012), and species persistence (Kondoh, 2006(Kondoh, , 2003Uchida and Drossel, 2007). Dynamic coupling of distinct food chains by an actively foraging top predator is regarded as important for community stability (e.g., Abrams, 2000;McCann et al, 2005;Rooney et al, 2008;Teng and McCann, 2004).…”
Section: Introductionmentioning
confidence: 99%